The The Effect of Resilience Reinforcement among the Elderly People in Amphoe Mueang, Nakhonsawan Province - Dekyong, Eakaluk; Inphen, Yuwaree; Changchua, Thattiya; Tongmuangtunyatep, Kanjananat (NU Journal of Nursing and Health Sciences, 2025)
This study was a quasi - experimental research using a one-group, pre-test/post-test design. The objective was to examine the effect of resilience reinforcement among the elderly people in Amphoe Mueang, Nakhonsawan Province. The sample consisted of 33 elderly people from Wat sai Subdistrict, Nakhonsawan Province, who passed the intellectual screening (Mini-Cog). The tools used in the study consisted of 2 parts: 1) the resilience reinforcement program, consisting of three dimensions withten activites for three times, one week apart and 2) data collection tools, including a general information form and a resilience reinforcement form for the elderly , developed by the Department of Mental Health, Ministry of Public Health, with a reliability coefficient of .90. the general information datawere analyzed by descriptive statistics and the hypothesis was tested by paired t-test.The results showed that a statistically significant increase in the overall mean score of resilience of the elderly after resilience reinforcement in the program (x̅ = 66.55, S.D. = 5.98) compared to before the intervention (x̅ = 60.33, S.D. = 5.98), with a p-value of < .001. Furthermore, by dimensions demonstrated significant improvements in emotional endurance (x̅ = 32.30, S.D. = 3.16, p = .001), motivation (x̅ = 17.82, S.D. = 2.36, p = .003), and problem-solving skills (x̅ = 16.42, S.D. = 2.77, p = .016) post-intervention.The results of this study showed that resilience reinforcement programs can increase resilience, or mental health strength, and can be used to further promote the abilities of the elderly.